Pemberdayaan Kewirausahaan Berbasis Teknologi Informasi Bagi Masyarakat Penyandang Disabilitas Di Gunung Kidul - Halim Budi Santoso; Argo Wibowo; Jong Jek Siang; Rosa Delima; Antonius Rachmat Chrismanto (Universitas Katolik Soegijapranata, 2021)
Information Technology has been implemented in some sectors in life. One of them is the usage of Information Technology for online commerce. Mitra Sejahtera Disabled Person Organization has some featured products which are sold locally in some places nearby and only in Gunung Kidul. The usage of Information Technology in marketing will help people to expand the basic consumer and market. On the other hand, Mitra Sejahtera Disabled Person Organization does not have enough access and ability to start and open online shop. Furthermore, the usage of the smartphone for member of Mitra Sejahtera Disabled Person Organization has not been optimal yet, like the utilization of social media as an official account. Training and empowerment activities to Mitra Sejahtera Disabled Person Organization will contribute in increasing and optimizing the utilization of social media and e-commerce. This training and empowerment activities also will give some knowledge to the participant about how to open online shop in one of the biggest online marketplace in Indonesia. The result of this activity is official account in media social. The participant also encouraged and trained to start online shop in one of the biggest online marketplace platform in Indonesia.